2001
DOI: 10.1007/s004970100088
|View full text |Cite
|
Sign up to set email alerts
|

Egg activation in flowering plants

Abstract: Compared to animals and algae, egg activation in flowering plants is still poorly understood because of the inaccessibility and complexity of the fertilization process which is double and internal. However, the development of in vitro fertilization (IVF) systems in maize and a few other plants, despite some limitations, offers new possibilities for the study of early postfusional events and signals leading to egg activation under defined conditions. This review reports recent data on calcium events induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…In Fucus, light also may reorient polarity (Goodner and Quatrano, 1993). In angiosperms, there is no such evidence of plasticity, nor is there any particular region on the female gamete that seems to be more receptive to fusion than any other region, at least according to in vitro studies (Antoine et al, 2001a). In vivo, however, position within the embryo sac appears to be an important factor in establishing both cellular identity and polarity.…”
Section: Egg Maturationmentioning
confidence: 99%
“…In Fucus, light also may reorient polarity (Goodner and Quatrano, 1993). In angiosperms, there is no such evidence of plasticity, nor is there any particular region on the female gamete that seems to be more receptive to fusion than any other region, at least according to in vitro studies (Antoine et al, 2001a). In vivo, however, position within the embryo sac appears to be an important factor in establishing both cellular identity and polarity.…”
Section: Egg Maturationmentioning
confidence: 99%
“…The Ca ++ influx occurs 1.8 s after the gamete fusion, and for a period of 24.4 min. Furthermore, using a combination method to simultaneously monitor the extracellular Ca ++ influx with a Ca ++ vibrating probe and cytoplasmic Ca ++ by wide‐field imaging, it has been observed that the fusion of the gametes is accompanied by a Ca ++ influx occurring 40–120 s before the transient increase of cytoplasmic Ca ++ concentration (Antoine et al 2000, 2001a; 2001b). Studies using a cell surface Ca ++ channel blocker, Cd +++ , have found that the inhibition of the Ca ++ influx does not affect the Ca ++ spike and the fusion of the sperm with the egg cell, but prevents the incorporation of their cytoplasm, suggesting that the Ca ++ spike may come from the release of Ca ++ from the intracellular compartment, rather than the Ca ++ influx.…”
Section: Ca++ Spike Is Critical For Pollen Tube Guidance and Zygotic mentioning
confidence: 99%
“…Studies using a cell surface Ca ++ channel blocker, Cd +++ , have found that the inhibition of the Ca ++ influx does not affect the Ca ++ spike and the fusion of the sperm with the egg cell, but prevents the incorporation of their cytoplasm, suggesting that the Ca ++ spike may come from the release of Ca ++ from the intracellular compartment, rather than the Ca ++ influx. The influx of Ca ++ is required for cytoplasm incorporation and karyogamy (Antoine et al 2001a, 2001b). Consistent with this observation, it has been observed during the in vitro fertilization of maize that calreticulin, a major Ca ++ storage protein, located in the lumen of ER, is strongly induced after fertilization (Dresselhaus et al 1996).…”
Section: Ca++ Spike Is Critical For Pollen Tube Guidance and Zygotic mentioning
confidence: 99%
“…As for the embryophytes, including the flowering plants and archegoniates, the female gametes are embedded in the female tissue. The cytological events of zygote formation in embryophytes are poorly understood (Antoine et al 2001). In ferns, Bell (1975) described some of the cytological processes of the nuclear fusion in Pteridium aquilinum .…”
Section: Introductionmentioning
confidence: 99%